PHARMACOTHERAPEUTIC EFFECTIVENESS OF COMPLEX HERBAL REMEDY “DIGDA-SHI-TAN” AT THE EXPERIMENTAL HEPATITIS - A. O. Zandanov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Hepatoprotective activity of herbal remedy at the experimental hepatitis was established. The herbal remedy digda-shi-tan decreases the content of TBA-active products in blood and tissues, increases activity of disintoxication function of liver and stimulates reparative processes in liver.